A fluorescent probe for Cd2+ based on a diarylethene with pyridinepiperazine-linked hydroxyquinoline group. Issue 23 (9th June 2016) - Duan, Fang; Liu, Gang; Liu, Peng; Fan, Congbin; Pu, Shouzhi
Abstract: A new diarylethene containing a pyridinepiperazine-linked hydroxyquinoline group was synthesized. Its multi-controllable switching behaviors induced by light and chemical stimuli were investigated. The diarylethene could be used as a fluorescent probe for the detection of Cd 2+ with high selectivity. When triggered by Cd 2+, enhanced fluorescence intensity accompanied with color change from light blue to bright blue was observed. In addition, the diarylethene exhibited notable fluorescence enhancement upon the addition of TFA into the solution. Moreover, its fluorescence behaviors in response to light and Cd 2+ were applied for the construction of a molecular logic circuit with four inputs and one output. Graphical abstract: Multi-controllable switching behaviors of an asymmetrical diarylethene with a pyridinepiperazine-linked hydroxyquinoline unit could be modulated by light, Cd 2+, and TFA/TEA.